Differences in smolt status affect the resistance of Atlantic salmon (Salmo salar L.) against infectious pancreatic necrosis, while vaccine-mediated protection is unaffected - Jensen, Ingvill (Journal of fish diseases, 2019)
© 2019 The Authors. Journal of Fish Diseases Published by John Wiley & Sons Ltd.